2019
DOI: 10.33369/atp.v3i2.10507
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Pembelajaran Learning Cycle 5e Pada Materi Hidrolisis Garam Di Kelas Xi Mipa Sman 1 Bengkulu Tengah Tahun Ajaran 2018/2019

Abstract: This study aims to determine the effect of the implementation of the 5E Learning Cycle learning model on increasing mastery of concepts in the subject matter of salt hydrolysis. This research was conducted at SMAN 1 Bengkulu Tengah in the 2018/2019 class XI MIP academic year in one meeting. The trial implementation of the 5E Learning Cycle model uses a pre-experimental research design with the form of one-group pretest-posttest design. The study was  conducted in February 2019 at SMAN 1 Bengkulu Tengah. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Based on research that has been done (Safitri et al, 2019) to get an increase in motivation after using the 5E Learning Cycle model where students in class XI MIPA 1 total 31 people from all aspects of the student response questionnaire obtained an average value of 4.2% with the category strongly agrees so that it can be concluded that students gave a good response to learning with the 5E Learning Cycle model. Research conducted Nurwahyu et al (2018)…”
Section: Introductionmentioning
confidence: 99%
“…Based on research that has been done (Safitri et al, 2019) to get an increase in motivation after using the 5E Learning Cycle model where students in class XI MIPA 1 total 31 people from all aspects of the student response questionnaire obtained an average value of 4.2% with the category strongly agrees so that it can be concluded that students gave a good response to learning with the 5E Learning Cycle model. Research conducted Nurwahyu et al (2018)…”
Section: Introductionmentioning
confidence: 99%